260 PRIORITY SETTING IN THE PROVINCIAL HEALTH SERVICES AUTHORITY: SURVEY OF KEY DECISION MAKERS. Issue 1 (1st January 2007) - Teng, F.; Mitton, C.; MacKenzie, J.
Abstract : Introduction: In recent years, decision makers in Canada and elsewhere have expressed a desire for more explicit, evidence-based approaches to priority setting. To achieve this aim within health care organizations, knowledge of both the organizational context and stakeholder attitudes toward priority setting is required. The current work adds to a growing body of international literature describing priority setting practices in health organizations. Methods: A qualitative study was conducted using in-depth, face-to-face interviews with 25 key decision makers of the Provincial Health Services Authority (PHSA) of British Columbia. Major themes and subthemes were identified and reported on through content analysis. Results: Priorities were described by decision makers as being set in an ad hoc manner, with resources generally allocated along historical lines. Participants identified the strategic plan and a strong research base as strengths of the organization. The main areas for improvement were a desire to have a more transparent process for priority setting, a need to develop a culture that supports explicit priority setting, and a focus on fairness in decision making. Barriers to an explicit allocation process included the challenge of providing specialized services for disparate patient groups and a lack of formal training in priority setting among decision makers. Conclusion: This study identified factors important to understanding organizational context and informed next steps for explicit priority setting for a provincial health authority. Although the PHSA is unique in its organizational structure in Canada, lessons about priority setting should be transferable to other contexts.